2020
DOI: 10.1007/s00784-020-03543-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, antimicrobial, and biological properties of White-MTAFlow

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
3
28
0
5
Order By: Relevance
“…Moreover, tantalum (Ta 5+ ) was detected both in NeoMTA 2 and NeoMTA Plus. A recent report described that the incorporation of Ta 5+ as an alternative radiopacifier does not cause discoloration and preserves acceptable values of radiopacity [ 30 ]. Also, Si 4+ release was detected in all ion-releasing materials after setting ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tantalum (Ta 5+ ) was detected both in NeoMTA 2 and NeoMTA Plus. A recent report described that the incorporation of Ta 5+ as an alternative radiopacifier does not cause discoloration and preserves acceptable values of radiopacity [ 30 ]. Also, Si 4+ release was detected in all ion-releasing materials after setting ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Testing soluble materials-such as reparative endodontic materials-over agar plates seems inappropriate once solubility halos are observed, indicating possible misleading interpretations [34]. Previous studies reported similar observations when testing hydraulic endodontic materials in contact with agar [67,68,75], reporting a limited antimicrobial effect of the reparative endodontic tested materials (Figure 2-Adapted from cited reference [74]); other studies using other methods such as confocal microscopy in contact with dentin and a mature biofilm [84] also concluded that previous disinfection of the site to be treated with these materials is crucial and mandatory in order to expect a positive clinical outcome. Different storage methods for antimicrobial testing can also obtain varying results; in water, for example, ProRoot MTA showed higher antimicrobial activity than when aged in blood and exhibited significant antimicrobial activity reduction after 7 days [35].…”
Section: Hydraulic Calcium Silicate-based Reparative Materialsmentioning
confidence: 83%
“…However, later studies indicated that the interaction of bismuth oxide with the collagen present in dental structures, together with the irrigating solution used during endodontic treatment of root canal therapy, were the main reasons for tooth pigmentation [62][63][64]. These studies resulted in the replacement of bismuth oxide with other substances such as calcium tungstate, zirconium oxide, and tantalum oxide serving as alternative radiopacifiers in compositions such as Biodentine (Septodont, Saint-Maur-des-Fossés, France), EndoSequence BC RRM Putty (Brasseler, Savannah, GA, USA), MTA Repair HP (Angelus, Londrina, Brazil), and White-MTAFlow (Ultradent Products Inc., South Jordan, UT, USA) [32,[65][66][67][68].…”
Section: Hydraulic Calcium Silicate-based Reparative Materialsmentioning
confidence: 99%
“…The absence of a specific ISO standard for hydraulic calcium silicate-based materials warrants the inclusion of previously reported methods in the general selection of tests, and the use of the ISO 6876:2012 standard (for endodontic sealers) to evaluate new compositions 7,9,11,12,18,25,26,27 such as Bio-C Pulpo. The inclusion of MTT cell culture testing with fibroblasts was used as a preliminary test for subcutaneous animal biocompatibility, considering the principles of the 3Rs (Replacement, Reduction, and Refinement) in research.…”
Section: Discussionmentioning
confidence: 99%
“…31 In the present study, the color assessment of the materials using the CIELab formula in contact with dentin used a previously reported method that evaluated MTA Angelus before the manufacturer replaced the bismuth oxide 7 with calcium tungstate in this radiopacifier. The use of the CIELab formula was preferred in the present study to allow comparison with previous studies 7,26 that used this method of analysis. The presence of bismuth oxide reported in that study resulted in considerably low L values and dentin staining in MTA Angelus samples.…”
Section: Discussionmentioning
confidence: 99%